Cyber Resilience in Banking A Practical Guide to Governance, Risk, and Compliance. - Young, Richard Gwashy (Productivity Press, 2026)
Drawing on the authors' experience as a cybersecurity practitioner, technology risk leader, and educator, he has crafted this series to bridge the gap between theoretical frameworks and practical applications in banking security.
Description based upon print version of record.
1.5 Implications for Enhancing Organizational Security Posture
Keywords: Banks and banking -- Data processing -- Security measures.; Banks and banking -- Computer networks -- Security measures.; Computer security.; elektronické knihy; electronic books